Corruption, Regulatory Burden and Firm Productivity - Amin, Mohammad; Ulku, Hulya (World Bank, Washington, DC, 2019)
Using firm-level data from more than 39,000 firms in 111 economies, this paper tests the hypothesis that corruption impedes productivity more at higher levels of regulation. The analysis finds that there is a significant negative relationship between corruption and firm productivity when regulation is high and an insignificant relationship when it is low. These findings are robust to different controls and specifications.